Investigation of thermal comfort under face masks wearing conditions in the smart building - Orman, Łukasz J.; Dębska, Luiza; Honus, Stanislav; Radek, Norbert; Adamczak, Stanisław; Siwczuk, Natalia (Frontiers in Built Environment, 2025)
The paper analyses thermal comfort of people wearing face masks. The study took place in the selected classrooms of the smart building “Energis” located in Poland. In the experiments 100 respondents participated. They filled in the questionnaire forms, in which they expressed their subjective assessment of the indoor thermal environment. Simultaneously, measurements of the physical parameters within the rooms were performed with a microclimate meter. The results clearly show that the use of face masks influenced thermal sensations of the people - they felt warmer than without the face mask on (at the same air temperature). Moreover, the respondents who wore the masks indicated that the air was more humid in relation to the case when the masks are not applied. The comparison of the obtained actual thermal sensations of the respondents with the calculation results according to the thermal comfort model proved that the model was unable to properly predict thermal sensations of people wearing face masks.